Maize and cover crop sequence in the Pampas: Effect of fertilization and water stress on the fate of nitrogen - Rimsky Korsakov Helena (2016)
Cover crops are well known for their positive effects on erosion processes, soil organicmatter, soil physical properties, weed populations and nitrate leaching. In this work, weevaluated the fate of nitrogen (N) from fertilizer in maize (Zea mays) and then inryegrass (Lolium multiflorum) as cover crop, in the conditions of the Argentine Pampas.To this end, a field experiment was carried out at the School of Agriculture, Universityof Buenos Aires, Argentina (34°36´ S, 58°29´ W). The design of the experiment was afactorial with three replications. We applied to maize 2 levels of N (0 and 140 kg N ha-1(125 lb N ac-1) (ammonium nitrate target with 15N) and two levels of water (50 and100% of crop evapotranspiration). 15N was determined in both the soil and plants.Maize plants and the soil organic fraction were the main sinks of fertilizer N, dependingon the water treatment. The N from fertilizer remaining as nitrates in the soil (0 to 1.50m [0 to 4.92 ft] depth) at maize harvest was 8% in plots subjected to water stresscompared to 3% in the non-water stressed. Nitrogen losses due to volatilization wereminor. Total N (soil and fertilizer) accumulated in ryegrass tissues plus nitratesremaining in the soil were higher in cover crop plots than in bare soil (130 vs. 51 kg Nha-1 [116 vs. 45.5 lb N ac-1]). The N in the soil organic matter originating from fertilizersignificantly decreased between maize harvest and cover crop harvest. This soilorganic N that originated from fertilizer mineralized at high rate (around 47% in 6months), suggesting it was in more labile. This mineralized N can be subjected topotential losses during following months.